URGENSI AKUNTANSI SYARIAH DALAM EKONOMI ISLAM MENURUT AL-QUR’AN DAN SUNNAH - Siska Lis Sulistiani (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2015)
ABSTRACT : Islamic economics is part of the fiqh muamalah grounded in the Qur'an and Sunnah, one of the domains Islamic economics are sharia accounting as one part to maintain accountability of economic activity of a Muslim either individually or in groups applied in the business world , Islamic banking, etc., so that factor accuracy, control, and record keeping in the context muamalah has been prescribed by the Quran and Sunnah. This study uses qualitative research methods to explore how literature studies (library research) with the level of descriptive study. This study shows that the urgency of sharia accounting is applied and developed in Islamic economic sector not only because of the level of their emergence in the field, but also have the spirit of faith because the value is based on the provisions of the Qur'an and Sunnah .